It runs in the family - Douglas, Michael, 1944-; Wigutov, Jesse; Schepisi, Fred.; Douglas, Kirk, 1916-; Culkin, Rory.; Douglas, Cameron, 1978-; Douglas, Diana, 1923-; Monaghan, Michelle; Peters, Bernadette; Baker, Ian, 1947-; Williams, Kate, 1967-; Grabowsky, Paul.; et al. ([United States] : MGM Home Entertainment, 2003)
Alex is trying to deal with a midlife crisis, while feeling caught in the middle of his familial obligations. While successful, Alex sometimes feels as if he's under the shadow of his father, Mitchell, a successful attorney. Mitchell has recently survived a stroke, and Alex and Mitchell want to mend their relationship while there's still time.
Special features: deleted scenes; making-of featurette; documentary of Kirk Douglas' career; director's audio commentary.
Director of photography, Ian Baker ; editor, Kate Williams ; music, Paul Grabowsky ; costume designer, Ellen Mirojinick ; production designer, Patrizia Von Brandenstein.
Michael Douglas, Kirk Douglas, Rory Culkin, Cameron Douglas, Diana Douglas, Michelle Monaghan, Bernadette Peters.
MPAA rating: PG-13; for drug content, sexual material and language.
DVD, Region 1 encoding, Dolby digital, DTS.
English, French or Spanish dialogue, French or Spanish subtitles; Closed-captioned.
Keywords: Fathers and sons -- Drama; Midlife crisis -- Drama; Cerebrovascular disease -- Patients -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired